THE ROLE OF DIGITAL TRANSFORMATION IN ENHACING THE ECONOMIC DEVELOPMENT OF SINGLE-PARENT FAMILIES: A LITERATURE REVIEW - Mirna PurnamaNingsih; Arlianty, Lia Shafira; Nastia, Gina Indah Permata; Fatimah, Sarah Nurul (Indonesian Journal of Social Work, 2024)
This paper explores the role of digital transformation in enhancing economic development within single-parent families. The study investigates how digital technologies contribute to economic empowerment, financial stability, and opportunities for single parents, ultimately influencing their overall economic well-being. The study also identifies challenges related to digital divides, access barriers, and the need for digital literacy among single-parent families. Literature review is conducted in this study to provide a comprehensive understanding of the impact of digital transformation on economic development in single-parent households. Overall, the research emphasizes that the digital transformation empowers single-parent families by providing access to flexible work, educational opportunities, financial tools, and social support networks, which may lead to improved economic outcomes and well-being. Recommendations for policymakers, organizations, and digital technology providers include promoting digital inclusion initiatives, expanding access to affordable digital services, and enhancing digital literacy programs tailored to the needs of single-parent households.